The tragedy of Macbeth - Shakespeare, William 1564-1616; Barnet, Sylvan ([New York] New American Library, 1963)
One of the great Shakespearean tragedies, Macbeth is a dark and bloody drama of ambition, murder, guilt and revenge. Prompted by the prophecies of three mysterious witches and goaded by his ambitious wife, the Scottish thane Macbeth murders Duncan, King of Scotland, in order to succeed him on the throne. This foul deed soon entangles the conscience-stricken nobleman in a web of treachery, deceit and more murders that ultimately spells his doom.
Suggested references p. 241-247.
Includes bibliographical references (pages 241-246)
Keywords: Macbeth -- King of Scotland -- active 11th century -- Drama; Drama